Analysis of Mental Nursing Care for Sensory Perception Disorder: Auditory Hallucinations with Thought Stopping Therapy - Diana Putri, Neng; Suryawantie, Tanti (CV. Literasi Publikasi Indonesia, 2026)
Mental disorders are conditions characterized by disharmonious relationships with others, hostility, threats, and often unproductivity. Hallucinations are false perceptions without external objects. This case study aimed to analyze the effect of Thought Stopping therapy on controlling auditory hallucinations in a patient with schizophrenia. A 54-year-old female patient (Mrs. P) with auditory hallucinations was included. Though stopping therapy was administered for 10-15 minutes per session, twice daily for 3 days. The intervention included teaching the patient to say “STOP” loudly and internally when hallucinatory thoughts appeared, then replacing negative thoughts with positive ones. Outcomes were measured by changes in hallucination frequency, duration, and patient’s ability to control hallucinations. Results showed a progressive decrease in hallucination frequency from 1-2 times daily to rarely occurring. The patient could perform thoughts, stopping independently by day 3. No adverse effects were observed. Thought stopping therapy effectively reduced auditory hallucination symptoms in this patient with schizophrenia. This non-pharmacological intervention is recommended as an adjunct therapy in mental health nursing care